diff -r dfcf3fa58d7f -r c8ef391dd6f7 twtsevms/twtsevms.tex --- a/twtsevms/twtsevms.tex Wed Mar 04 13:25:52 2020 +0000 +++ b/twtsevms/twtsevms.tex Fri Apr 10 11:58:11 2020 +0100 @@ -1,13 +1,12 @@ \documentclass[a4paper,UKenglish]{lipics} +\usepackage{data} \usepackage{graphic} -\usepackage{data} \usepackage{tikz-cd} \usepackage{tikz} %\usetikzlibrary{graphs} %\usetikzlibrary{graphdrawing} %\usegdlibrary{trees} - %\usepackage{algorithm} \usepackage{amsmath} \usepackage{xcolor} @@ -15,7 +14,7 @@ \usepackage{enumitem} \usepackage{nccmath} \usepackage{soul} - +%works? \definecolor{darkblue}{rgb}{0,0,0.6} \hypersetup{colorlinks=true,allcolors=darkblue} \newcommand{\comment}[1]% @@ -102,30 +101,38 @@ If we let the alphabet where $c$ is selected from be $\sum = \{0,1\}$, -then bitcodes can be defined in a -regular expression style: +then we can define the regular expression +style bitcodes: -\[ bs ::= \ZERO \mid \ONE +\[ rbs ::= \ZERO \mid \ONE \mid 1 \mid 0 - \mid bs_1 \cdot bs_2 - \mid \sum{bs_{list}} - \mid bs^* + \mid rbs_1 \cdot rbs_2 + \mid \sum{rbs_{list}} + \mid rbs^* \] -We can define an isomorphism between the regex -definition of bitcodes and our list definition of bitcodes: +This is our list definition of bitcodes: +\begin{center} +$b ::= 1 \mid 0 \qquad +bs ::= [] \mid b::bs $ +\end{center} + +Define an isomorphism between bitcodes based on lists +and bitcodes based on regular expressions: \begin{center} - $b ::= 1 \mid 0 \qquad -bs ::= [] \mid b::bs -$ +\begin{tabular}{lcl} +$\sigma: bit \; list$ & $\Rightarrow$ & $bit \; regex$\\ +$\delta: bit$ & $\Rightarrow$ & $bit \; regex$\\ +$\sigma([])$ & $=$ & $ \ONE$\\ +$\sigma(b::bs)$ & $=$ & $\delta(b) \cdot \sigma(bs)$\\ +$\delta(b) $ & $=$ & $b\; as \;a \;regex$ +\end{tabular} \end{center} -For example we can let $\sigma([])= \ONE$. -But how to define such isomorphism in detail is not explicitly needed for now. \emph{Annotated regular expressions} can be defined by the following -grammar using new $bs$ definition: +grammar using the list definition of $bs$ : \begin{center} \begin{tabular}{lcl} @@ -137,23 +144,75 @@ & $\mid$ & $_{bs}a^*$ \end{tabular} \end{center} -Let the set of all bitcoded regular expressions be $\textit{BS}$. -Let the set of all annotated regular expression be $\textit{AR}$. -Let us play with the function $f: \textit{AR} \rightarrow \textit{BS}$ on annotated regular expressions: +%Let the set of all bitcoded regular expressions be $\textit{BS}$. +%Let the set of all annotated regular expression be $\textit{AR}$. +Let us play with the function $f: \textit{annotated}\; \textit{regex} \Rightarrow \textit{bit}\; \textit{regex}$ on annotated regular expressions: \begin{center} -$f(\ZERO) = \ZERO$\\ -$f(_{bs}\ONE) = \textit{bs}$\\ -$f(_{bs}a) = \textit{bs} $\\ -$f(_{bs}r_1\cdot r_2) = \textit{bs} \cdot( f(r_1) \cdot f(r_2))$\\ -$f(_{bs}\sum{rs}) = \textit{bs} \cdot \sum\limits_{r \in rs}{f(\textit{r})}$\\ -$f(_{bs}r^*) = \textit{bs} \cdot((0 \cdot f(r))^*\cdot 1) $ +\begin{tabular}{lcl} +$f(\ZERO)$ & $=$ & $\ZERO$\\ +$f(_{bs}\ONE)$ & $=$ & $\sigma(\textit{bs})$\\ +$f(_{bs}a)$ & $=$ & $\sigma(\textit{bs}) $\\ +$f(_{bs}r_1\cdot r_2)$ & $=$ & $\sigma(\textit{bs}) \cdot( f(r_1) \cdot f(r_2))$\\ +$f(_{bs}\sum{rs})$ & $=$ & $\sigma(\textit{bs}) \cdot \sum\limits_{r \in rs}{f(\textit{r})}$\\ +$f(_{bs}r^*)$ & $=$ & $\sigma(\textit{bs}) \cdot((0 \cdot f(r))^*\cdot 1) $ +\end{tabular} +\end{center} + +Now define function $L: bit\;regex \Rightarrow set \; bs$ as follows: +\begin{center} +\begin{tabular}{lcl} +$L(\ZERO)$ & $=$ & $\emptyset$\\ +$L(\ONE) $ & $= $ & $\{[]\}$\\ +$L(b\;as \; a\;regex) $ & $=$ & $\{b\; as \; a \; bit\}$\\ +$L(bs_1 \cdot bs_2)$ & $=$ & $L(bs_1) \times L(bs_2)$\\ +$L(\sum bss) $ & $=$ &$\bigcup\limits_{bs \in bss}{L(bs)}$\\ +$L(bs^*)$ & $= $ & $\bigcup\limits_{0 \leq n}{(L(bs))^n}$ +\end{tabular} \end{center} We claim that: \begin{center} -$f(a) = \{bs \mid a \gg bs\}$. +$L(f(a) )= \{bs \mid a \gg bs\}$. \end{center} +where contains is defined this way: +\begin{center} +\begin{tabular}{llclll} +& & & $_{bs}\ONE$ & $\gg$ & $\textit{bs}$\\ +& & & $_{bs}{\bf c}$ & $\gg$ & $\textit{bs}$\\ +$\textit{if} \; r_1 \gg \textit{bs}_1$ & $r_2 \; \gg \textit{bs}_2$ +& $\textit{then}$ & + $_{bs}{r_1 \cdot r_2}$ & + $\gg$ & + $\textit{bs} @ \textit{bs}_1 @ \textit{bs}_2$\\ + + $\textit{if} \; r \gg \textit{bs}_1$ & & $\textit{then}$ & + $_{bs}{\sum(r :: \textit{rs}})$ & + $\gg$ & + $\textit{bs} @ \textit{bs}_1 $\\ + + $\textit{if} \; _{bs}(\sum \textit{rs}) \gg \textit{bs} @ \textit{bs}_1$ & & $\textit{then}$ & + $_{bs}{\sum(r :: \textit{rs}})$ & + $\gg$ & + $\textit{bs} @ \textit{bs}_1 $\\ + + $\textit{if} \; r \gg \textit{bs}_1\; \textit{and}$ & $_{bs}r^* \gg \textit{bs} @ \textit{bs}_2$ & $\textit{then}$ & + $_{bs}r^* $ & + $\gg$ & + $\textit{bs} @ [0] @ \textit{bs}_1@ \textit{bs}_2 $\\ + + & & & $_{bs}r^*$ & $\gg$ & $\textit{bs} @ [1]$\\ +\end{tabular} +\end{center} + +Moreover, we claim the fact that +\begin{center} + $L(f(a^*)) != L(f(a^* \backslash a))$ +\end{center} +This is by $\exists bs \in f(a^*), s.t. bs \notin f(a^* \backslash a)$. +Proof for the fact +$L(f(a) )= \{bs \mid a \gg bs\}$: + \bibliographystyle{plain} \bibliography{root}